Chemical and physical characterization of stabilized polyacrylonitrile (pan) fiber. - Salleh, S.N.M. (EDP Sciences, 2014)
Fibers Stabilization is an exothermic process which involves heat treatment at lower temperature from 150 °C to 300 °C. It is considered as a crucial step that will determine the final structure of the carbon fibre and its mechanical properties. This work involves comparison of physical and mechanical properties of Polyacrylonitrile (PAN) and stabilized Polyacrylonitrile (PAN) fiber produced from batch process. The functional group of the fibre was studied using ATR-FTIR and the morphology was characterised by AFM and SEM. Mechanical properties of the fibers will be studies using single column tensile machine with ASTM D3822 testing procedure. The studies show significant change of physical and mechanical properties of Polyacrylonitrile (PAN) and stabilized Polyacrylonitrile (PAN) fiber. This lead to different application for every type of fibers produced before and after stabilization process. © 2014 Owned by the authors, published by EDP Sciences.